Evidence of Calcium Signaling and Modulation of the LmrS Multidrug Resistant Efflux Pump Activity by Ca2 + Ions in S. aureus - Nava, Amy R.; Mauricio, Natalia; Sanca, Angel J.; Domínguez, Delfina C. (Frontiers in Microbiology, 2020)
Calcium ions (Ca2+) play a pivotal role in eukaryote cell signaling and regulate many physiological functions. Although a similar role for Ca2+ in prokaryotes has been difficult to demonstrate, there is increasing evidence for Ca2+ as a cell regulator in bacteria. The purpose of this study was to investigate Ca2+ signaling and the effect of Ca2+ on the Staphylococcus aureus multidrug resistant efflux pump LmrS. We hypothesized that antibiotics act by increasing Ca2+ concentrations, which in turn enhance the efflux activity of LmrS. These Ca2+ transients were measured by luminometry in response to various antibiotics by using the photoprotein aequorin reconstituted within live bacterial cells. Efflux associated with LmrS was measured by the increase in fluorescence due to the loss of ethidium bromide (EtBr) from both S. aureus cells and from E. coli cells in which the lmrs gene of S. aureus was expressed. We found that addition of antibiotics to cells generated unique cytosolic Ca2+ transients and that addition of CaCl2 to cells enhanced EtBr efflux whereas addition of Ca2+ chelators or efflux pump inhibitors significantly decreased EtBr efflux from cells. We conclude that antibiotics induce a Ca2+ mediated response through transients in cytosolic Ca2+, which then stimulates LmrS efflux pump.